STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH PERILAKU VERBAL BULLYING - Anis Fauzi; Ahmad Izza Muttaqin (MUMTAZ : Jurnal Pendidikan Agama Islam, 2024)
This research is motivated by a phenomenon of student behavior in junior high Darussyafa'ah Setail Genteng there are still many students who do verbal bullying activities. Because such behavior is very contrary to the teachings of Islam, moral and ethical values in education. Included in SMP Darussyafa'ah Setail Genteng very strict rules in terms of combating bullying because in this case it is taken from one of the visions of SMP Darussyafa'ah Setail Genteng that is the birth of a generation that berahlakul karimah so as to meet the needs of society and the nation. However, from all the principles and visions above are very contrary to the reality that occurs, it was found that in SMP Darussyafa'ah there are still many students who commit acts of bullying behavior, especially verbal bullying. In this study researchers describe the findings that are shared data and the uniqueness-the uniqueness found in the field. This study uses qualitative descriptive method. In the process of data collection using several methods, namely observation, interview and documentation methods and for the data analysis process in this study contains three main components, namely data reduction, data presentation and draw conclusions. The results of the study can be concluded that the strategy of Islamic Religious Education Teachers in preventing verbal bullying behavior is a way used by Islamic Religious Education teachers to prevent verbal bullying in the school environment. One of the strategies that teachers of Islamic Religious Education do at SMP Darussyafa'ah Setail Genteng is to inculcate Islamic values, emphasis in character education, exemplary method of Islamic religious education teacher, provide punishment as a deterrent effect. The form of verbal bullying is by calling friends by calling their parents ' names, there are also those who call with rude calls such as fools, fools, and others. this happens during empty hours, recess, or when there is no supervision from the teacher in the classroom. Supporting factors in preventing verbal bullying behavior are school environment factors and teacher education factors. While the inhibitory factors are friend factors and habit factors that can affect student behavior.